Legal Protection Efforts of Employees Through the Social Security Administration Agency - Rasji, Rasji; Wardhana, Adi Pratomo Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Legal protection efforts for workers in Indonesia through the Social Security Agency on Health (BPJS) are one of the strategic steps in ensuring worker welfare, both in the formal and informal sectors. This study aims to analyze the company's obligation to register its workers in BPJS membership and the legal protection efforts that can be provided through social security programs organized by BPJS Kesehatan and BPJS Ketenagakerjaan. First, the company's obligation to register its workers in BPJS membership is regulated in Law Number 24 of 2011 concerning BPJS, which mandates that every company is required to register all its workers in the social security program. Although there are clear legal provisions, implementation in the field still faces challenges such as low awareness from some companies and workers themselves. Second, legal protection efforts for workers through BPJS can be seen from two main aspects, namely health insurance and employment insurance. The health insurance program provides protection for workers and their families from unexpected health risks, while employment insurance provides protection against socio-economic risks faced by workers, such as work accidents, death, or retirement. With this program, workers have the right to obtain health services and financial compensation that can ease the burden of life due to the occurrence of these risks. This study reveals that although BPJS plays an important role in providing legal protection for workers, there are challenges in its implementation, such as gaps in equal access to services and non-compliance by several companies with registration obligations. Therefore, stricter supervision, increased legal awareness, and stricter law enforcement are needed against companies that do not register their workers with BPJS. With these steps, it is hoped that the social security program can run effectively and provide maximum protection for workers in Indonesia.